IFNAR1 Deficiency Impairs Immunostimulatory Properties of Neutrophils in Tumor-Draining Lymph Nodes - Hussain, Timon; Domnich, Maksim; Bordbari, Sharareh; Pylaeva, Ekaterina; Siakaeva, Elena; Spyra, Ilona; Ozel, Irem; Droege, Freya; Squire, Anthony; Lienenklaus, Stefan; Sutter, Kathrin; Hasenberg, Anja; et al. (Frontiers in Immunology, 2022)
Tumor-draining lymph nodes (TDLNs) are the first organs where the metastatic spread of different types of cancer, including head and neck cancer (HNC), occurs and have therefore high prognostic relevance. Moreover, first immune responses against cancer are initiated in such LNs via tumor-educated myeloid cells. Among myeloid cells present in TDLNs, neutrophils represent a significant population and therefore considerably participate in the activation of effector lymphocytes there. Tumor-supportive or tumor-inhibiting activity of neutrophils strongly depends on the microenvironment, e.g. type I IFN availability primes anti-tumor activity of these cells. In accordance, mice deficient in type I IFNs show the accumulation of pro-tumoral neutrophils, elevated tumor growth, and metastatic spread. To reveal the mechanism responsible for this phenomenon, we have studied here the influence of defective type I IFN signaling on the immunoregulatory activity of neutrophils in pre-metastatic tumor-draining LNs. Live imaging of tumor-draining, pre-metastatic LNs was performed using two-photon microscopy in a transplantable murine head and neck (HNC) model. CatchupIVM-red x C57BL/6, CatchupIVM-red x Ifnar1-/- mice were used to visualize neutrophils and to assess their interaction with T- cells in vivo. We have evaluated spatiotemporal patterns of neutrophil/T-cell interactions in LNs in the context of IFNAR1 availability, in both: tumor-free and tumor-bearing animals. Moreover, phenotypic and functional analyses were performed to further characterize the mechanisms regulating neutrophil immunoregulatory capacity in the context of IFN availability. We demonstrated that inactive IFNAR1 on neutrophils results in their elevated accumulation in TDLNs. However, these neutrophils show significantly impaired capacity to interact and stimulate T-cells. As a result, a significant reduction of contacts between neutrophils and T lymphocytes was observed, with further impairment of T-cell proliferation and activation. This possibly contributes to the enhanced tumor growth in Ifnar1-/- mice. In agreement with our hypothesis, IFNAR1-independent activation of IFN signaling using IFN- improved the immunostimulatory capacity of neutrophils in TDLNs and contributed to the suppression of tumor growth. Our results suggest that type I IFN signaling is essential for neutrophil immunostimulatory capacity and that stimulation of this signaling may provide a therapeutic opportunity in head and neck cancer patients.